Ward D - McFadden, Freida ([Place of publication not identified] : [publisher not identified], 2023)
Medical student Amy Brenner has dreaded her required overnight rotation assigned to Ward D, the hospital's locked inpatient mental health unit, so when patients and staff being to disappear during her shift, Amy is convinced her worst fears are coming true.
Keywords: Women medical students -- Fiction; Hospital wards -- Fiction; Psychiatric hospital care -- Fiction; Missing persons -- Fiction; Psychological fiction; Thrillers (Fiction)